Depression, Nutrition, and Adherence to Antiretroviral Therapy in Men Who Have Sex With Men in Manila, Philippines - Elsayed, Hend; O'Connor, Cara; Leyritana, Katerina; Salvana, Edsel; Cox, Sharon E. (Frontiers in Public Health, 2021)
Introduction: Depression is the most frequently observed psychiatric disorder among HIV. The effect of depression on adherence among MSM HIV patients has not been well studied in the Philippines. Depression is commonly undiagnosed and consequently untreated which leads to a negative influence on ART adherence. Other risk factors such as HIV-related stigma, self-body image satisfaction, and nutritional status are recognized as a potential barrier to access HIV prevention and treatment services issues and poor adherence. Methods: Hospital Anxiety and Depression Scale (HADS) was used to screen depressive symptoms during scheduled clinic visits. ART adherence was self-reported using a visual analog scale questionnaire covering the last 30 days. Structured questionnaires were used for measuring risk factors and socio-demographic data. Anthropometry was conducted and body composition assessed using bio-electrical impedance analysis (BIA). Results: One-hundred and ninety-three participants were recruited from the SHIP clinic between 7th March to 30th September 2018, of whom, 42 (21.8%) screened positive for depression (HADS score ≥8) and 24 (12.4%) were nonadherent to ART (<95% of medication taken as prescribed). The most common reported reason for nonadherence was simply forgotten (18 out of 42, 42.9%). Increasing depressive symptoms were associated with nonadherence (crude odds ratio (OR)=1.13; 95%CI: 1.02-1.26). Social Family Support (SFS) and Body Image (BI) scores were also associated with nonadherence but were not statistically significant in multivariable models. Factors significantly associated with depressive symptoms (but not nonadherence) included: using intravenous drugs, being in a relationship, anxiety, self-esteem, and stigma scores. Conclusions: Increased depression symptoms, low social family support, and body image dissatisfaction may be inter-connected risk factors for ART nonadherence among Filipino MSM HIV patients. Comprehensive mental health services beyond regular post-HIV testing counseling may increase adherence to ART and improve HIV treatment outcomes. Further prospective studies are needed to address the causal/ reverse causal pathway between depression and nonadherence.